KEWIRAUSAHAAN PEMUDA MALAYSIA: MENUMBUHKAN SEMANGAT BERWIRAUSAHA DI USIA MUDA - Saputra, Andrian; Rizky, Tengku Muhammad; Akbar, Rayhan (Al-Sharf: Jurnal Ekonomi Islam, 2024)
This paper discusses entrepreneurship among the younger generation in Malaysia. The main strategy of the agenda for national development is from the economic sector, one of which is entrepreneurship. Therefore, in several related matters, the role of the government itself is how to improve the entrepreneurial sector or known as MSMEs so that they can be encouraged to be developed for the community. With the hope that new entrepreneurs will emerge, sectors of the community's economy will be able to grow and become more established, therefore other sectors such as education and health can be properly guaranteed. The research method used in this article is qualitative using a creative economy approach. The method of extracting through the data that has been used is through structured interviews and literature study. The research results show that some of the youth in Malaysia have an interest and interest in the world of business and entrepreneurship. Thus, there is already an awareness of developing an entrepreneurial spirit. Thus, all parties are expected to become agents of change for the improvement in the economic sector and MSMEs. Through various kinds of programs carried out by the government and also the campus, thus trying to become agents to grow new entrepreneurs with special hopes, namely young people in Malaysia.